Improving effectiveness of learning through class activity assessment : a case study - Chia, Yeng *; Norashimah Abdul Jalil, * (Sunway University College, 2010)
Most education reformers agree that effective learning in the classroom is based on both teachers? and students? co-operation and creativity in generating a good learning atmosphere. Many educational institutions are exploring new dimensions in class activity and assessment which not only complement the curriculum but form an integral part it. Reports have shown that in today?s environment, scoring straight As will not necessary guarantee a student a place in university or in the working sector. Rather, students require greater exposure especially through having class activities and assessments inside and outside the classroom such as talks, workshops, seminars, forums and field trips. Such activities can improve the effectiveness of the students? learning process, and will not only contribute towards a higher final subject grade, but also better prepare the pre-university students for their next stage of education in the university. This paper therefore focuses on the steps that could be taken to improve the effectiveness of learning through class activities and assessments. Specifically, it aims to gain feedback from students and lecturers at the preuniversity level on how such activities can be conducted and assessed to improve the learning and teaching processes. The authors also investigate some possible activities that can fulfill this purpose such as the methods of assessment, challenges encountered by lecturers and students, and possible solutions. The information is mainly distilled from a survey conducted on students and staff involved in the Mathematics-Science and Social Sciences subjects taught in the Canadian International Matriculation Programme (CIMP).